Upaya Perpustakaan Dalam Menghadapi Tindakan Vandalisme Bahan Pustaka Di Perpustakaan Umum Daerah Kabupaten Lima Puluh Kota - Oktaviani, Tia; Nabila, Jeihan (Universitas Negeri Padang, 2023)
Vandalism is a violation of rules in the library, which includes deleting, tearing, and other actions that damage collections. This study aims to identify forms of vandalism that occur in The Library of Lima Puluh Kota and its prevention efforts. The study uses a qualitative method with a descriptive approach. Data was collected through observation, interviews, and documentation, then analyzed by data reduction and drawing conclusions. The results showed that the vandalism that occurred at The Library of Lima Puluh Kota included returning books past the deadline, deleting and tearing of pages, and using other people's Library Membership Cards. Librarians have made various prevention efforts, such as reminding the return schedule, giving warnings and sanctions, improving security systems and conservation preservation. However, obstacles occur due to limited facilities and infrastructure due to budget constraints, as well as time constraints for librarians in carrying out activities to prevent vandalism of library materials